Інноваційні підходи до інформаційного забезпечення наукових досліджень - Веретеннікова, Наталія; Кунанець, Наталія Едуардівна (Видавництво Львівської політехніки, 2017)
The aim of the study is to analyze the leading role of libraries in the information support of virtual organizations that conduct research on the platform of e-science. It is introduced the concept of virtual creative team and its characteristics.
Keywords: електронне інформаційне середовище; віртуальний науковий колектив; е-наука; інформаційно- комунікаційна інфраструктура; наукова комунікація